Development of ICT TPACK learning media for gymnastics material - Komang Eka Triasa; Made Agus Wijaya; I Made Satyawan (Universitas Sriwijaya, 2023)
ICT TPACK-oriented Physical Education learning media is an urgent matter at this time. This study aimed to develop a video task of forward fold, balance, and jumping for elementary school students by adopting the ADDIE model design. This article focused on the analysis and planning phases. The research population consisted of a total number of students 683. This study took a sample of 448 students in 5 public elementary schools in the Buleleng District. The research instrument used a closed questionnaire in the form of a Google Form and a motion task validation sheet. The analysis technique used quantitative-qualitative descriptive analysis. Based on the study's results, it was found that 1) 96.9% (448 people) of students needed Physical education videos for learning motion tasks. 2) the content expert scored 69 from the highest score, 75. Based on the research and discussion results, this research could be concluded: 1) Elementary School Physical education teachers needed a motion task video and carried it out according to this study 2) The motion task was considered valid by Physical education content experts.